Relationship between Stress Level, Body Mass Index (BMI), and Smoking Behavior with Severity of Psoriasis at Hospital X in Central Lombok Region - Sajjad, Fiqhan Syauki; Handayani, Wendy; Mariam, Lysa; Mulianingsih, Wiwin (Jurnal Biologi Tropis, 2024)
Psoriasis is an inflammatory skin disease of the erythrosquamous dermatosis group, related to autoimmune, chronic and relapsing (recurring) nature influenced by genetic and environmental factors as its pathogenesis. Psoriasis cases are increasingly common, although psoriasis is not immediately life-threatening, it causes cosmetic disorders that greatly affect the quality of life of sufferers. This study aims to determine the relationship between stress levels, Body Mass Index (BMI), and smoking behavior with the severity of psoriasis at Hospital X in Central Lombok. This study employs an observational analytic approach with a cross-sectional design. The data were examined univariately and bivariately. The study found a strong correlation between stress levels and psoriasis severity at Hospital X in Central Lombok (p = 0.002). There is a significant link between BMI and the severity of psoriasis at Hospital X in Central Lombok with a p value of 0.006. At Hospital X in Central Lombok, there is a substantial correlation (p value of 0.000) between smoking behavior and the severity of psoriasis.